A Prospective Determination of the Incidence of Perceived Inappropriate Care in Critically Ill Patients. Issue 3 (2014) - Singal, Rohit K; Sibbald, Robert; Morgan, Brenda; Quinlan, Mel; Parry, Neil; Radford, Michael; Martin, Claudio M
Abstract : BACKGROUND: Health care providers' perceptions regarding appropriateness in end-of-life treatments have been widely studied. While nurses and physicians believe that rationing and other cost-related practices sometimes occur in the intensive care unit (ICU), they allege that treatment is often excessive. OBJECTIVE: To prospectively determine the incidence and causes of health care providers' perceptions regarding appropriateness of end-of-life treatments. METHODS: The present prospective study collected data from patients admitted to the medical-surgical trauma ICU of a 30-bed, Canadian teaching hospital over a three-month period. Daily surveys were completed independently by bedside nurses, charge nurses and attending physician. RESULTS: In total, 5224 of 6558 expected surveys (representing 294 patients) were analyzed, yielding a response rate of 79.7%. The incidence of perceived inappropriate care in the present study was 6.5% (19 of 294 patients), with ongoing treatment for >2 days after this determination occurring in 1% (three of 294 patients). However, at least one caregiver perceived inappropriate care at some point in 110 of 294 (37.5%) patients. In these cases, in which processes to address care were not already underway, respondents believed that important issues resulting in provision of inappropriate treatments included patient-family issues and communication before or in the ICU. Caregivers did not know their patients' wishes 22% (1129 of 5224) of the time. CONCLUSIONS: Although ongoing inappropriate care appeared to be a rare occurrence, the issue was a concern to at least one caregiver in one-third of cases. Public awareness for end-of-life issues, adequate communication, and up-to-date knowledge and practice in determining the wishes of critically ill patients are potential target areas to improve end-of-life care and reduce inappropriate care in the ICU. A daily, prospective survey of multidisciplinary caregivers, such as the survey used in the present study, is a viable and valuable means of determining the scope and causes of inappropriate care in the ICU.